Kontrasepsi Suntik 3 Bulan Mempengaruhi Kenaikan Berat Badan Ibu - Fenniokha, Nabela Gyandra; Susilawati, Susilawati; Kurniasari, Devi; Evayanti, Yulistiana (Universitas Malahayati Bandar Lampung, 2022)
Background The contraception that is mostly chosen by acceptors in Indonesia is 61.4% injectable contraception, but injection contraception has an impact that can cause weight gain. acceptors revealed that by using injectable contraception they felt it was more practical in the family planning process. The purpose of the study was to find the effect of 3-month injection contraception on maternal weight gain in Puskesmas Gedong Air Bandar Lampung in 2020. Methods This type of quantitative research, analytical research design with true experiment approach with two group posttest only design with control group design population in this study were all 804 family planning askreceptors, 40 samples divided into 2 groups, simple random sampling technique, this research has conducted in July 2020. data collection using observation sheets. Univariate and bivariate data analysis t-test (t-test). The results showed that the mean increase in body weight for 3 months injection family planning acceptors was 3,7 kg, the mean increase in body weight for 1 month injection family planning acceptors was 1,8 kg. Conclusion There is no effect of 3-month injection contraception on maternal weight gain at the Gedong Air Bandar Lampung Community Health Center in 2020, the statistical test results obtained p-value = 0.016 (pvalue> α = 0.05). Suggestion Health workers are expected to be able to provide counseling for hormonal contraceptive acceptors, especially injections to be able to switch to long-term nonhormonal contraceptives such as IUDs. Key words: body weight, contraception, 3 months injection,Kontrasepsi yang banyak dipilih oleh akseptor di Indonesia adalah kontrasepsi suntik sebanyak 61,4%, namun kontrasepsi suntik memiliki dampak yang dapat menyebabkan penambahan berat badan. akseptor mengungkapkan dengan menggunakan kontrasepsi suntik mereka merasa lebih praktis dalam proses KB. Tujuan penelitian diketahui Pengaruh Kontrasepsi Suntik 3 Bulan Terhadap Kenaikan Berat Badan Ibu Di Puskesmas Gedong Air Bandar Lampung Tahun 2020. Metode : Jenis penelitian kuantitatif, desain penelitian analitik dengan pendekatan true eksperimen dengan rancangan two group postest only With Control group design populasi dalam penelitian ini adalah seluruh askseptor KB sebanyak 804, sampel sebanyak 40 yang dibagi 2 kelompok, tekhnik sampling secara simple random sampling, penelitian ini telah di lakukan bulan Juli 2020. pengumpulan data dengan lembar observasi. Analisa data univariat dan bivariat uji t (t-test). Hasil penelitian Diketahui mean peningkatan berat badan akseptor KB Suntik 3 bulan seberat 3,7 Kg, mean peningkatan berat badan akseptor KB Suntik 1 bulan seberat 1,8 Kg. Kesimpulan Tidak ada Pengaruh Kontrasepsi Suntik 3 Bulan Terhadap Kenaikan Berat Badan Ibu Di Puskesmas Gedong Air Bandar Lampung Tahun 2020, hasil uji statistik didapatkan p-value = 0,016 (p-value > α = 0,05). Saran tenaga kesehatan diharapkan dapat memberikan konseling pada akseptor kontrasepsi hormonal khususnya suntik untuk bisa beralih kekontrasepsi nonhormonal jangka panjang seperti IUD. Kata kunci: berat badan kontrasepsi, suntik 3 bulan